Peran Pengetahuan dan Kekuasaan dalam Implementasi PTN-BH di Indonesia - Rohmah, Putri Adibatur; Muhammad, Ardiyana; Utami, Dinda Dwi; Maulana, Ilham Nur Hanifan (Universitas Al Azhar Indonesia, 2024)
Higher education institutions (HEIs) are establishments that offer education, instruction, research, and services across fields of science and technology. Autonomy, in management, categorizes state universities (PTNs) based on their structure. State universities with status (PTN-BH) hold the position in resource management within the campus hierarchy of state universities. This study adopts an approach incorporating a literature review methodology and analysis through Michel Foucault's theory on the interplay between power and knowledge. This study aims to understand how power shapes the identity and norms of universities and to analyze the dynamics of HEIs in the context of economic priorities and their implications for democracy. The findings indicate that power influences the regulation of knowledge creation presenting both challenges and opportunities for PTN-BH. Michel Foucault's theory underscores how power shapes university identities and norms. The evolution of PTN-BH signifies a transition towards prioritizing concerns, over welfare, impacting democratic ideals.Keywords – Knowledge, Michel Foucault, Power, PTN-BH